Thermal resistance of aluminum gravity heat pipe with threaded capillary structure - Nikolaenko, Yu. E.; Kozak, D. V. (Technology and design in electronic equipment, 2017)
The results of an experimental study of the thermal resistance of an aluminum gravitational heat pipe with isobutane (R600a) as a working fluid under conditions of heat removal of natural air convection are presented. Comparison of the thermal resistance of an aluminum gravitational heat pipe with a threaded capillary structure and the thermal resistance of an aluminum thermosyphon of the same size, having a smooth surface of the body in the evaporation zone, is given. It is shown that in the range of values of the input heat flux from 5 to 50 W the thermal resistance of the gravitational heat pipe is substantially lower than the thermal resistance of the thermosiphon. The studies were conducted both without the use of additional radiators in the condensation zone of heat transfer devices, and with the use of one, two and three radiators.